If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23h + -89 = 63 + 42h Reorder the terms: -89 + 23h = 63 + 42h Solving -89 + 23h = 63 + 42h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-42h' to each side of the equation. -89 + 23h + -42h = 63 + 42h + -42h Combine like terms: 23h + -42h = -19h -89 + -19h = 63 + 42h + -42h Combine like terms: 42h + -42h = 0 -89 + -19h = 63 + 0 -89 + -19h = 63 Add '89' to each side of the equation. -89 + 89 + -19h = 63 + 89 Combine like terms: -89 + 89 = 0 0 + -19h = 63 + 89 -19h = 63 + 89 Combine like terms: 63 + 89 = 152 -19h = 152 Divide each side by '-19'. h = -8 Simplifying h = -8
| 5ln(4x-2)-16=9 | | x^4+11x^3-44=0 | | 16x-19=113-6xz | | 63d-44=-140+47d | | 3x^2+x-1900=0 | | 63d-44=140+47d | | -21+6x=33+9x | | 12-3x/x^2-8x+16 | | 5(g-2)+g=6g-24 | | x=log(3)15 | | x^4+11x^2-44=0 | | x^2+11x^2-44=0 | | 14j-53=73+32j | | 2n/n^2-3n | | -14p+51=57p+23 | | t-1/t^2+t | | 75+21k=19+29k | | -80=b-91 | | x(7-x)+2whenx=-4 | | 20=t-70 | | 4(x+8)-7whenx=8 | | lg(x+3)+lg(1-x)=lg(4x+8) | | v-4.7=23.8 | | 59+19f=8f+5 | | k-16=7 | | 15=c-40 | | 2+n=95 | | -54=c-38 | | a-33=66 | | 19r+39=9+4r | | -16-7x=208-42x | | 8000(d)=-5d^2+450d-1000 |